Challenges and complication management in novel artificial iris implantation - Mayer, Christian; Laubichler, Andrea E.; Khoramnia, Ramin; Tandogan, Tamer; Prahs, Philipp; Zapp, Daniel; Reznicek, Lukas (Journal of ophthalmology, 2018)
Purpose: Evaluation of postoperative artificial iris prosthesis-related complications. - Design: Retrospective cohort study. - Methods: Fifty-one consecutive patients underwent pupillary reconstruction using an artificial iris implant made from silicone between 2011 and 2015. Quantity and quality of complications were subclassified into three groups including mild, moderate, and severe complications. Their management and the learning curve were evaluated. - Results: In total, 13 (25.5%) of 51 included artificial iris implantations showed unexpected events in various degrees: mild complications: recurrent bleeding (n=1, 2.0%), slight but stable iris deviation (n=1, 2.0%), capsular fibrosis (n=2, 3.9%); moderate complications: suture cutting through the residual iris (n=1, 2.0%), glaucoma (n=3, 5.9%), and corneal decompensation (n=3, 5.9%); severe complications: artificial iris suture loosening (n=2, 3.9%) and dislocation (n=3, 5.9%), synechiae (n=2, 3.9%), glaucoma (n=2, 3.9%), and corneal decompensation (n=5, 9.8%) with the need for surgery, cystoid macular edema (n=3, 5.9%) and retinal detachment (n=1, 2.0%). The complication rate decreased from 83.3% (5 of 6 implantations) in the first year to 13.3% (2 of 15 implantations) in the 4th year. Nineteen of 45 evaluated patients showed a significant gain in best-corrected visual acuity (BCVA) from 1.09 ± 0.56 logMAR to 0.54 ± 0.48 logMAR (p < 0.001), and 13 of 45 eyes had a significant BCVA loss from 0.48 ± 0.39 logMAR to 0.93 ± 0.41 logMAR after surgery (p < 0.001). - Conclusions: The artificial iris is a feasible option in the treatment of iris defects with a wide spectrum of postoperative complications. The significant reduction of complications after twelve implantations implicates that the procedure is not to be recommended in low volume settings.
Gesehen am 23.03.2020